Catalytic Asymmetric Synthesis of 2, 6‐Disubstituted Cuneanes through Enantioselective Constitutional Isomerization of 1, 4‐Disubstituted Cubanes. Issue 37 (11th July 2022) - Takebe, Hiyori; Matsubara, Seijiro
Abstract: 2, 6‐Disubstituted cuneane has potential as a p ‐disubstituted benzene bioisostere and a novel chiral scaffold. It is a constitutional isomer of a 1, 4‐disubstituted cubane obtained via a metal‐catalyzed skeletal rearrangement. Unlike the highly symmetrical 1, 4‐disubstituted cubane, the isomerized 2, 6‐disubstituted cuneane is a chiral molecule possessing C 2 symmetry. Examining various chiral catalysts revealed that the Pd‐pincer catalyst provides a good asymmetric induction. Abstract : 2, 6‐Substituted cuneanes were obtained by metal‐catalyzed isomerization of 1, 4‐disubstituted cubanes and are stable cage‐like hexahedral compounds with C 2 v symmetry. In this process, the chiral cage‐like hexahedral hydrocarbon in one step. The asymmetric induction was performed using chiral P−C−P pincer Pd catalyst. The obtained cuneane will be a novel chiral scaffold.